Variations In Methods For Storing Samples From Diabetes Mellitus Patients On The Results Of Urine Leukocyte Examination - Maulidiyah , Hikmatul; Puspitasari (Universitas Nahdlatul Ulama Surabaya, 2024)
Diabetes mellitus (DM) is often accompanied by both microvascular and macrovascular. One of the common complications in patients with diabetes mellitus is a urinary tract infection. The purpose of this study was to determine the difference between using a 10% formaldehyde preservative and storage at 4°C to delay urine leukocyte examination in diabetic patients. This study employed an analytical observationalmethod using urine samples from patients with diabetes mellitus. A total of six samples were obtained from Siti Fatimah Tulangan 'Aisyiyah Hospital. The research was conducted from May to June 2023. The results indicate that there are differences in the results of urine leukocyte examinations in diabetes mellitus patients based on the variations in sample storage methods. Keywords: Delayed, diabetes mellitus, leukocytes, storage, urine.